Aging of the Human Vestibular System - Zalewski, Christopher K. (Seminars in Hearing, 2015)
Aging affects every sensory system in the body, including the vestibular system. Although its impact is often difficult to quantify, the deleterious impact of aging on the vestibular system is serious both medically and economically. The deterioration of the vestibular sensory end organs has been known since the 1970s; however, the measurable impact from these anatomical changes remains elusive. Tests of vestibular function either fall short in their ability to quantify such anatomical deterioration, or they are insensitive to the associated physiologic decline and/or central compensatory mechanisms that accompany the vestibular aging process. When compared with healthy younger individuals, a paucity of subtle differences in test results has been reported in the healthy older population, and those differences are often observed only in response to nontraditional and/or more robust stimuli. In addition, the reported differences are often clinically insignificant insomuch that the recorded physiologic responses from the elderly often fall within the wide normative response ranges identified for normal healthy adults. The damaging economic impact of such vestibular sensory decline manifests itself in an exponential increase in geriatric dizziness and a subsequent higher prevalence of injurious falls. An estimated $10 to $20 billion dollar annual cost has been reported to be associated with falls-related injuries and is the sixth leading cause of death in the elderly population, with a 20% mortality rate. With an estimated 115% increase in the geriatric population over 65 years of age by the year 2050, the number of balanced-disordered patients with a declining vestibular system is certain to reach near epidemic proportions. An understanding of the effects of age on the vestibular system is imperative if clinicians are to better manage elderly patients with balance disorders, dizziness, and vestibular disease.
Keywords: Vestibular; aging; presbystasis; presbyvertigo; presbyequilibrium; geriatric dizziness